Scaling-up recombinant enzyme fermentation - Azmi, Azlin Suhaida; Sulaiman, Sarina; Mohamed Azmin, Nor Fadhillah; Ali, Fathilah (Springer International Publishing, 2015)
Bioreactor or fermenter is the heart of a process. Scaling up a bioreactor and maintaining the same optimized process in a recombinant enzyme production in a higher scale is an engineering challenge. Scale-up is about mixing and mass transfer, a combination of art and science. It is more to methodological approach with some combination of rules of thumb, experience and/or trial and error. This chapter presented several bioreactor or fermenter modes and types before encompasses four different scale-up strategies. The scale-up strategies related to mass transfer involving constants scale-up of; (i)volumetric transfer coefficient (KLa), (ii) power input per liquid volume (P/V), (iii) impeller tip speed (Vi), and (iv) mixing time (t m) are described and discussed.